Age, Sex and Seasonal Variations of Vitamin D Level in Children of Jammu Region - Rachna Sabharwal; Pallavi Mahajan (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Vitamin D deficiency is considered as one of the most common undiagnosed medical conditions in the world. Studies from India have reported prevalence of vitamin D deficiency varying from 30 to 100%. Among children, vitamin D deficiency can affect skeletal growth and development. A 25- hydroxyvitamin D (25(OH)D) provides single best assessment of vitamin D status as it has a half life of about 3 weeks, making it suitable indicator of vitamin D status. Aim: This cross-sectional study was conducted to find out the prevalence of vitamin D deficiency in healthy children ≤ 15 years of age and their relation with seasonal variation. Materials and Methods: Laboratory data of 25(OH)D was prospectively collected from apparently healthy children aged 7 days to 15 years in the Government Medical College, Jammu, India. Serum vitamin D was analysed by Chemiluminiscent microparticle immunoassay. Serum 25(OH)D level <5 ng/ml was considered severe vitamin D deficiency, 5-10 ng/ml as moderate and 10-20 ng/ml as mild hypovitaminosis. The data was analysed with the help of SPSS version 20. Results: It was observed that out of total 150 children, prevalence of vitamin D deficiency (25-(OH)-D < 15 ng/ml) was present in 76 (50.67%) and insufficiency in 63 (42%) children. Ten children (6.67%) had severe vitamin D deficiency (< 5 ng/ ml), 22 (14.67%) children had moderate hypovitaminosis (5-10 ng/ml) and 107 (71.33%) had mild (10-20 ng/ml). Only 11 (7.33%) children had normal levels of serum 25(OH)D (>20 ng/ ml). The mean serum 25(OH)D concentrations were significantly lower from October to March (Winter) as compared from April to September(Summer) in children. Conclusion: Vitamin D deficiency was observed among the younger age group. Thus adequate awareness among the masses should be done about the exposure of sunlight, dietary rich sources of vitamin D and fortification of foods with vitamin D for prevention and control of vitamin D deficiency.